Antara Tangguhan dan Transparansi: Peran Moderasi Sustainability Reporting dalam Menekan Agresivitas Pajak - Halimah, Imar; Sanulika, Aris; Hidayati, Wahyu Nurul (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Corporate tax aggressiveness has become a critical issue in recent years, raising concerns about transparency and ethical financial practices. Companies often engage in various strategies to minimize tax burdens, including the use of deferred tax components and selective disclosure in sustainability reporting. This study aims to analyze the influence of Deferred Tax Expense (DTE), Deferred Tax Asset (DTA), and Sustainability Reporting (SR) on tax aggressiveness, and to examine the moderating role of SR in these relationships. A quantitative approach was employed using multiple linear regression and Moderated Regression Analysis (MRA). The sample consisted of 26 companies selected through purposive sampling from a population of 130 companies, based on the availability of complete financial and sustainability reports for the 2019–2023 period. The results show that, partially, only SR has a significant negative effect on tax aggressiveness. In contrast, DTE and DTA do not have a significant impact. Furthermore, MRA results indicate that SR does not significantly moderate the relationship between DTE, DTA, and tax aggressiveness. These findings suggest that sustainability reporting practices have not yet functioned effectively as a control mechanism in corporate tax avoidance strategies. This study contributes to strengthening corporate fiscal transparency and encourages more substantive sustainability disclosures.